A contextual review of the Carnivora of Kanapoi. Issue 140 (March 2020) - Werdelin, Lars; Lewis, Margaret E.
Abstract: The Early Pliocene is a crucial time period in carnivoran evolution. Holarctic carnivoran faunas suffered a turnover event at the Miocene-Pliocene boundary. This event is also observed in Africa but its onset is later and the process more drawn-out. Kanapoi is one of the earliest faunas in Africa to show evidence of a fauna that is more typical Pliocene than Miocene in character. The taxa recovered from Kanapoi are: Torolutra sp., Enhydriodon (2 species), Genetta sp., Helogale sp., Homotherium sp., Dinofelis petteri, Felis sp., and Parahyaena howelli . Analysis of the broader carnivoran context of which Kanapoi is an example shows that all these taxa are characteristic of Plio-Pleistocene African faunas, rather than Miocene ones. While some are still extant and some went extinct in the Early Pleistocene, P. howelli is unique in both originating and going extinct in the Early Pliocene.